Biological factor related to Asian sand dust particles contributes to the exacerbation of asthma. Issue 5 (7th October 2016) - Honda, Akiko; Sawahara, Takahiro; Hayashi, Tomohiro; Tsuji, Kenshi; Fukushima, Wataru; Oishi, Mizuki; Kitamura, Gaku; Kudo, Hitomi; Ito, Sho; Yoshida, Seiichi; Ichinose, Takamichi; Ueda, Kayo; et al.
Abstract : Epidemiologic studies have revealed that Asian sand dust particles (ASDs) can affect respiratory and immune health represented by asthma. Factors responsible for the exacerbation of asthma remain unclear. The fungus Bjerkandera adusta ( B.ad ) and polycyclic aromatic hydrocarbons such as benzo[ a ]pyrene (BaP) have been identified in ASDs collected from the atmosphere when an ASD event occurred. We investigated the effects of B.ad and BaP related to ASDs on respiratory and immune systems. Bone marrow‐derived antigen‐presenting cells (APCs) and splenocytes from atopic prone NC/Nga mice and human airway epithelial cells were exposed to the B.ad or to BaP in the presence and absence of heated‐ASDs (H‐ASDs). B.ad and BaP in both the presence and absence of H‐ASDs increased the expression of cell surface molecules on APCs. H‐ASDs alone slightly activated APCs. The expressions induced by B.ad were higher than those induced by BaP in the presence and absence of H‐ASDs. There were no remarkable effects on the activation of splenocytes or the proinflammatory responses in airway epithelial cells. These results suggest that B.ad rather than BaP contributes to the exacerbation of asthma regardless of the presence or absence of sand particles, particularly by the activation of the immune system via APCs. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Bjerkandera adusta ( B.ad ) and benzo[ a ]pyrene (BaP) each activated antigen‐presenting cells (APCs) in the presence and the absence of heated Asian sand dust particles (H‐ASDs). H‐ASDs alone slightly activated APCs. The activation induced by B.ad was more apparent than that by BaP in the presence and absence of H‐ASDs. B.ad rather than BaP contributes to the exacerbation of asthma regardless of the presence or absence of sand particles, particularly by activation of the immune system via APCs.